Analysis of Poverty in Indonesia - Yuliansyah, Yuliansyah (Budapest International Research and Critics University, 2022)
Destination from the study this study aims to determine the development of poverty in Indonesia and determine the poverty level between provinces in Indonesia in the 2016-2020 period. The method used is descriptive qualitative with secondary data, namely data on the poverty line, number, and poverty level in Indonesia from the Central Statistics Agency for the 2016-2020 period. Based on results analysis, extreme poverty in Indonesia decreased from March 2016 – to March 20-19 but increased in 2020 due to Covid-19.